Predictors of medications-free and long-term remission in anti-neutrophil cytoplasmic antibody-associated vasculitis: Real-world evidence - Babapoor, Parvin; Hajialilo, Mehrzad; rahimi, Mehran; Esalatmanesh, kamal; Rahmanpour, Dara; Barahimi, Ali; Khabbazi, Alireza (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: In this study, we report the outcomes of anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) in daily practice based on Connective Tissue Diseases Research Center-Vasculitis Registry (CTDRC-VR) data. Methods: Patients were included if they were 18 years or older, had a diagnosis of the groups of AAV based on 2022 American College of Rheumatology/European Alliance of Associations for Rheumatology Classification Criteria for granulomatosis with polyangiitis, eosinophilic granulomatosis with polyangiitis and microscopic polyangiitis, and were followed for a period longer than 2 years or were died. Complete clinical remission was defined as granulomatosis with polyangiitis (BVAS/GPA) of 0. Sustained remission was defined as a complete clinical remission for at least six months and tapering prednisolone dose to ≤ 7.5 mg/d. Long-term remission was defined as complete clinical remission for ≥ 5 years and tapering prednisolone dose to ≤ 7.5 mg/d. Medications-free remission was defined as complete clinical remission and discontinuation of glucocorticoids, cytotoxic medications and biologics. Results: Sixty patients with AAV were enrolled in this study. Sustained and long-term remission were developed in 91.7 and 72.1 percent of patients, respectively. Relapse was developed in 27 (45%) patients. Medications-free remission was developed in 23 (33.3%) patients. Vasculitis induced damage was developed in 40 (66.7%) patients. Patients with damage had significantly lower age and higher BVAS at the baseline. Upper airway and renal involvement, and non-adherence in patients with damage was significantly more common. Conclusions: Induction therapy leads to long-term and medications-free remission in 72% and 38% of patients with AAV, respectively.